PENGELOLAAN PENGUNJUNG PADA ANDALUS WISATA KELUARGA KABUPATEN KAMPAR - Reza, Muhammad; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The progress and development of a tourist attraction is always accompanied by good management methods. Among the most important is the management of visitors given attractions ranging from before visiting, during a visit and after a visit. Andalus Family Tourism is a tourist attraction that has its own way of managing visitors. This study aims to find out how to manage visitors in the Family Tourism Andalus. This research uses descriptive qualitative method to analyze the problem based on interview data collection techniques, observation, and documentation which are then drawn conclusions. The subject of this study was obtained from the results of interviews with key informants, namely, the deputy chairman of the Andalus Family Tourism management. And the results of the research carried out, it appears that the manager of the Family Tourism Andalus shows that management specifically for managing visitors is still in the starting stage and looks simple. Management is still focused on tourist attractions. So that it has not made this tourist attraction a halal tourist attraction. Keywords: Management